Human atlas ([United States], 2005)
This interactive CD-ROM offers 150 3D animations and 3D models of human conditions and treatments
Keywords: Giải phẫu người,Dịch tễ học,Human anatomy,Diseases,Epidemiology; Tập hình ảnh,Atlases